Evaluation of Radiopacity of Bulk-fill Flowable Composites Using Digital Radiography - (:unkn) unknown (OPERATIVE DENTISTRY INC, 2016)
New flowable composites that may be bulk-filled in layers up to 4 mm are indicated as a base beneath posterior composite restorations. Sufficient radiopacity is one of the several important requirements such materials should meet. The aim of this study was to evaluate the radiopacity of bulk-fill flowable composites and to provide a comparison with conventional flowable composites using digital imaging. Ten standard specimens (5 mm in diameter, 1 mm in thickness) were prepared from each of four different bulk-fill flowable composites and nine different conventional flowable composites. Radiographs of the specimens were taken together with 1-mm-thick tooth slices and an aluminum step wedge using a digital imaging system. For the radiographic exposures, a storage phosphor plate and a dental x-ray unit at 70 kVp and 8 mA were used. The object-to-focus distance was 30 cm, and the exposure time was 0.2 seconds. The gray values of the materials were measured using the histogram function of the software available with the system, and radiopacity was calculated as the equivalent thickness of aluminum. The data were analyzed statistically (p<0.05). All of the tested bulk-fill flowable composites showed significantly higher radiopacity values in comparison with those of enamel, dentin, and most of the conventional flowable composites (p<0.05). Venus Bulk Fill (Heraeus Kulzer) provided the highest radiopacity value, whereas Arabesk Flow (Voco) showed the lowest. The order of the radiopacity values for the bulk-fill flowable composites was as follows: Venus Bulk Fill (Heraeus Kulzer) >= X-tra Base (Voco) > SDR (Dentsply DeTrey) >= Filtek Bulk Fill (3M ESPE). To conclude, the bulk-fill flowable restorative materials, which were tested in this study using digital radiography, met the minimum standard of radiopacity specified by the International Standards Organization.
Keywords: RESTORATIVE MATERIALS; RESIN-COMPOSITES; SECONDARY CARIES; MECHANICAL-PROPERTIES; DIAGNOSIS; SYSTEMS; CAVITIES; CEMENTS